UpSMART: five years of digital innovation in cancer clinical research—achievements, challenges, and recommendations - O’Regan, Paul; Butt, Fouziah; Carter, Louise; Graham, Donna M.; Le Blanc, Anja; Hoskins, Richard; Stephenson, Laura; Patil, Akshita; Shabbir, Muhammad; Eken, Dilan; Singh, Subir; Villa, Andrea; et al. (Frontiers in Digital Health, 2025)
UpSMART, a research programme involving 24 European cancer centres, aimed to promote digital innovation in early-phase clinical research addressing challenges in recruitment, data collection and analysis. Several open-source digital healthcare products (DHPs) were developed through UpSMART, including eTARGET and trialFinder for trial matching, and PROACT 2.0 for patient-reported data. Lessons learned highlight the importance of multidisciplinary teams, sustainable funding and deployment, and engagement with the research community to maximise impact.